Home rehabilitation system for the upper extremity focusing on technology-aided assessment of spasticity - Panny Matthias; Nagiller Ines; Nagiller Marco; Kim Yeongmi (Current Directions in Biomedical Engineering, 2022)
This paper presents a robotic wrist rehabilitation device that facilitates both pronation/supination and flexion/ extension movements. Further, it provides technologyaided assessment capabilities through measurement of joint stiffness, range of motion (ROM) and detection of the catch that is often associated with spasticity. The mechanical and electrical system design, allowing for aforementioned training and assessment capabilities, is presented. An indirect torque measurement via the actuator currents is proposed, which can determine the angle of catch, and compared to the already established methods of using inertial measurement units. The approach is tested using a simplified, mechanical model of the joint catch on the presented device. The results show that the indirect measurement has similar performance of assessing the angle of catch as the inertial data. Therefore, the presented device shows a potential to assess not only stiffness but also the angle of catch without additional sensors.